Experimental use of apramycin against broiler colibacillosis - ΔΟΝΟΣ ΑΝΔΡΕΑΣ (Journal of the Hellenic Veterinary Medical Society, 2019)
Apramycin was evaluated for the prevention and treatment of colibacillosis in broilers. Administered in the drinking water at a dose level of 0.5g/l for 5 days it controled and treated the septicaemic form of colibacillosis. Given at 0.25g/l drinking water the first 5 days of life of broiler chicks it prevented death losses which were caused by pathogenic strains of E. coli. Thus, apramycin, reduced the economical production costs of broiler from «problematic» hatcheries